A Medal for Benny Movie Still - Paramount Pictures:::Creator::::::::::::
Zach Mibbe (Charles Dingle), Charley Martin (J. Carrol Naish), Lolita Sierra (Dorothy Lamour), and Edgar Lovekin (Frank McHugh) in Paramount Pictures' 'A Medal for Benny.' John steinbeck wrote the original story for the screen RESTRICTED USE Digital copy only. No hard copy.